Immunogenomic analysis reveals LGALS1 contributes to the immune heterogeneity and immunosuppression in glioma. Issue 2 (22nd January 2019) - Chen, Qun; Han, Bo; Meng, Xiangqi; Duan, Chunbin; Yang, Changxiao; Wu, Zhenyu; Magafurov, Dinislam; Zhao, Shihong; Safin, Shamil; Jiang, Chuanlu; Cai, Jinquan
Abstract : Mutualistic and dynamic communication between tumour cells and the surrounding microenvironment accelerates the initiation, progression, chemoresistance and immune evasion of glioblastoma (GBM). However, the immunosuppressive mechanisms of GBM has not been thoroughly elucidated to date. We enrolled six microenvironmental signatures to identify glioma microenvironmental genes. The functional enrichment analysis such as ssGSEA, ESTIMATE algorithm, Gene Ontology, Pathway analysis is conducted to discover the potential function of microenvironmental genes. In vivo and in vitro experiments are used to verify the immunologic function of LGALS1 in GBM. We screen eight glioma microenvironmental genes from glioma databases, and discover a key immunosuppressive gene ( LGALS1 encoding Galectin‐1) exhibiting obviously prognostic significance among glioma microenvironmental genes. Gliomas with different LGALS1 expression have specific genomic variation spectrums. Immunosuppression is a predominate characteristic in GBMs with high expression of LGALS1 . Knockdown of LGALS1 remodels the GBM immunosuppressive microenvironment by down regulating M2 macrophages and myeloid‐derived suppressor cells (MDSCs), and inhibiting immunosuppressive cytokines. Our results thus implied an important role of microenvironmental regulation in glioma malignancy and provided evidences of LGALS1 contributing to immunosuppressive environment in glioma and that targeting LGALS1 could remodel immunosuppressive microenvironment of glioma. Abstract : What's new? When a glioblastoma (GBM) develops in the CNS, immunosuppressive cytokines allow the tumor to evade and suppress the immune system. They also prevent current immunotherapies from effectively attacking the tumor. In this study, the authors found that variations in the gene coding for the cytokine Galectin‐1 may provide a prognostic biomarker in GBM. They also found that blocking this gene reduces immunosuppression in the GBM microenvironment. These results help to explain why immunosuppression is a hallmark of GBMs, and may also lead to improved immunotherapies for this aggressive tumor.